Risk of Severe Bleeding With Extended Rivaroxaban to Prevent Venous Thromboembolism in Acute Medically Ill Patients With Bronchiectasis. (October 2021) - Lipardi, Concetta; Elliott, C. Gregory; Sugarmann, Chiara L.; Haskell, Lloyd; Spyropoulos, Alex C.; Raskob, Gary E.; Xu, Jianfeng; Lu, Wentao; Marsigliano, Jessica; Spiro, Theodore; Yuan, Zhong; Wu, Shujian; et al.
Background: Bronchiectasis is a chronic inflammation of the bronchi with recurrent infections and hemoptysis. The MAGELLAN study compared oral rivaroxaban, 10 mg once daily (QD), for 35 ± 4 days with subcutaneous enoxaparin 40 mg QD for 10 ± 4 days followed by placebo for 25 ± 4 days to prevent venous thromboembolism in patients hospitalized with an acute medical illness. MAGELLAN included a subset of patients with bronchiectasis. In a post hoc analysis, we evaluated the incidence and severity of pulmonary bleeding in patients with bronchiectasis who were hospitalized for an acute medical illness. This analysis included MAGELLAN patients diagnosed with bronchiectasis at baseline. Patients were evaluated by treatment group for International Society on Thrombosis and Haemostasis major bleeding, non-major clinically relevant (NMCR) bleeding, and the composite of the 2 (ie, clinically relevant bleeding).Results: Medically ill patients with bronchiectasis were randomized to rivaroxaban (n = 60) or enoxaparin/placebo (n = 61). There were 2 fatal pulmonary bleeds and 1 fatal gastrointestinal bleed in the rivaroxaban arm and no fatal or major bleeding in the enoxaparin/placebo arm. The incidence of major bleeding was 5% in the rivaroxaban arm. One NMCR bleed occurred in the rivaroxaban arm and 2 NMCR bleeds occurred in the enoxaparin/placebo arm. The incidence of clinically relevant bleeding was 6.7% versus 3.3% in the rivaroxaban and enoxaparin/placebo groups, respectively (relative risk = 2.06 [95% confidence interval: 0.351-12.046]).Conclusion: In-patients hospitalized with bronchiectasis and an acute medical illness, clinically relevant bleeding, including fatal pulmonary hemorrhage, occurs more frequently with extended rivaroxaban thromboprophylaxis than with enoxaparin followed by placebo.